Preliminary Notes on the Physician Krateuas (2nd–1st Century BC). A New Collection of his T and F - Squillace, Giuseppe (Studia Ceranea, 2021)
The physician Krateuas lived in the first part of the 1st century BC, worked at the court of Mithridates and wrote a Rhizotomikon (Herbal) of which only a few fragments remain. More than a century ago, Max Wellmann studied this physician (1897; 1898) and collected his Testimonies (T) and Fragments (F) as an appendix of his edition of Dioscorides De materia medica (1914). After Wellmann, only short studies (mostly encyclopedia entries) have been carried on Krateuas, whose work influenced Dioscorides. This paper is a first step towards a monograph on this physician and a new edition of T and F with translation and historical commentary.